Ultralow-power near-infrared excited neodymium-doped nanoparticles for long-term in vivo bioimaging. Issue 14 (27th March 2017) - Qin, Qing-Song; Zhang, Pei-Zhi; Sun, Ling-Dong; Shi, Shuo; Chen, Nai-Xiu; Dong, Hao; Zheng, Xiao-Yu; Li, Le-Min; Yan, Chun-Hua
Abstract : Core@shell structured LiLuF4 :Nd@LiLuF4 nanoparticles with efficient near-infrared emission were used for in vivo bioimaging under ultralow-power-density excitation (10 mW cm −2 ). Abstract : Lanthanide-doped luminescent nanoparticles with both emission and excitation in the near-infrared (NIR-to-NIR) region hold great promise for bioimaging. Herein, core@shell structured LiLuF4 :Nd@LiLuF4 (named as Nd@Lu) nanoparticles (NPs) with highly efficient NIR emission were developed for high-performance in vivo bioimaging. Strikingly, the absolute quantum yield of Nd@Lu NPs reached as high as 32%. After coating with polyethylene glycol (PEG), the water-dispersible Nd@Lu NPs showed good bio-compatibility and low toxicity. With efficient NIR emission, the Nd@Lu NPs were clearly detectable in tissues at depths of up to 20 mm. In addition, long-term in vivo biodistribution with a high signal-to-noise ratio of 25.1 was distinctly tracked upon an ultralow-power-density excitation (10 mW cm −2 ) of 732 nm for the first time.